The Implementation of East Java Provincial Government Policy In The Development of Madrasah Diniyah - Ismail, Ismail; Fahruddin, Ahmad Hanif (Jurnal Review Politik, 2021)
In decentralization era, local government has been always aiming to serve an effective and efficient public policy. Effectiveness and efficiency of a public policy is considered by not solely by its policy formulation, but mainly by its implementation. An effective and efficient public policy is a course that can be implemented well and right, thus the expected purpose can be achieved at its maximum potency. Provincial government of East Java has been widely-known after their public policies related to development of Madrasah Diniyah, therefore this research focused on matters as followed: (1) What is the form of East Java provincial government policy on Madrasah Diniyah development? (2) How is the implementation of East Java provincial government policy on Madrasah Diniyah development? (3) What is the implementation model of East Java provincial government policy on Madrasah Diniyah development? Like most qualitative research, this research applies the methods of interview, observation and documentation in collecting research data. Then the analysis is carried out through data reduction, data presentation, and drawing conclusions. This study obtained several findings such as: (1) The form of East Java provincial government policy on Madrasah Diniyah development, including: (a) Madrasah Diniyah teachers quality enhancement programme, and (b) Implementation Funding Programme for Diniyah Education and Private Teachers; (2) The implementation of East Java provincial government policy on Madrasah Diniyah development involved policy stakeholders of both bureau and non-bureau, and (3) The implementation model of East Java provincial government policy on Madrasah Diniyah development was Hybrid Society Endorsement.